Palladium-Catalyzed Cross-Coupling Reactions of Cyclopropanols - Rosa, David; Nikolaev, Andrei; Nithiy, Nisha; Orellana, Arturo (Synlett, 2015)
Strained alcohols have featured prominently in a wide array of transition-metal-catalyzed cross-coupling reactions, but methods involving cyclopropanols have only been developed relatively recently. In this account, we describe our group’s work in this area, and we provide a concise summary of other palladium-catalyzed methods for C–C bond-forming reactions using cyclopropanols.1 Introduction2 Cross-Coupling Reactions Using Strained Tertiary Alcohols3 Base- or Acid-Mediated Ring-Opening Reactions of Strained Alcohols4 Palladium-Catalyzed Cross-Coupling Reactions of Cyclopropanols4.1 Palladium-Catalyzed Cross-Coupling Reactions of Cyclopropanols with Aryl Halides4.2 Palladium-Catalyzed Cross-Coupling Reactions of Cyclopropanols with Benzyl Halides4.3 Palladium-Catalyzed Cross-Coupling Reactions of Cyclopropanols with Acyl Halides4.4 Direct Arylation Using Cyclopropanol-Derived Palladium Homoenolates4.5 Synthesis of Quinolines from Cyclopropanols5 Conclusions
Keywords: palladium; cross-coupling; cyclopropanols; strain; C–C cleavage; homoenolates